Measuring Health Status in Long-Term Residential Care: Adapting the Veterans RAND 12 Item Health Survey (VR-12©). Issue 3 (27th May 2022) - Wilson, Rozanne; Cuthbertson, Lena; Kazis, Lewis; Sawatzky, Richard
ABSTRACT: Objectives : Measuring the perceived mental and physical health status of older adults living in long-term residential care (LTRC) is central to patient-centered care. This study examined the qualitative content validity of the Veterans RAND 12 Item Health Survey (VR-12) for LTRC and, based on the findings, the authors developed an adapted version of the generic patient-reported outcome measure for this population. Methods : Content validity was evaluated in two steps: (1) initial resident feedback (n = 9) and research team consensus discussions and (2) cognitive interviews with residents (n = 18) and a research team consensus discussion. The cognitive interviews examined comprehension, acceptability, and relevance of the VR-12 items. Results : Two VR-12 items had limited acceptability in the LTRC setting, the reference to " work " in items was irrelevant to residents, and the lack of a frame of reference (" During the past week … ") impacted comprehension of several items. Conclusions : Study findings informed the development of an adapted version of the VR-12 for older adults living in Canadian LTRC homes and provided content validity evidence regarding its relevance and appropriateness for this population. Clinical implications : Measuring the health status of older adults living in LTRC can help to monitor changes in health status over time and support person-centered care.